Investigating Audience Empowerment Through User-Generated Content Practice in Online Media Platforms - Putri, Ardhanareswari A Handoko (Jurnal Komunikasi, 2022)
In the contemporary media sphere, newsrooms are urged to transform the exclusive editorial culture into an inclusive working environment to enable collaboration between journalists and audiences. Thus, UGC has become common practice to build a participatory space where the audiences function as active participants. However, the current UGC practice has strengthened the dilemma of audiences in journalism. On the one hand, media organisations are obliged to serve the ‘citizens’ as a part of the press's significant role in the realm of democracy. Nevertheless, at the same time, media organisations also have to operate as profit-based entities in order to survive financially. In this context, the audiences are treated as ‘consumers’ from whom the profit is derived. By utilising the concept of ‘participatory journalism’ and the audience empowerment in journalism, this article aims to capture the UGC practice in the media in Indonesia and how it affects the audiences; whether it merely serves the media as a part of business strategy or the practice also aspires to empower the audiences. This qualitative study case focuses on three mainstream online media in Indonesia, namely Kumparan, IDN Times, and Detikcom. This study finds that while the empowering UGC practice begins to appear, the general practice of UGC indicates that it is a mere business strategy. In other words, audiences are deemed as ‘consumers’ rather than ‘citizens.’ Thus, this current situation creates a ‘false sense of participation’ in participatory journalism practice.